Effects of electroacupuncture on the levels of retinal gamma-aminobutyric acid and its receptors in a guinea pig model of lens-induced myopia. (26th February 2015) - Sha, F.; Ye, X.; Zhao, W.; Xu, C.-L.; Wang, L.; Ding, M.-H.; Bi, A.-L.; Wu, J.-F.; jiang, W.-J.; Guo, D.-D.; Guo, J.-G.; Bi, H.-S.
Highlights: The levels of retinal GABA, GABAA and GABAC receptors are up-regulated in myopia. EA inhibits the up-regulation of retinal GABA, GABAA and GABAC receptors in myopia. The effect of EA at Hegu and Taiyang acupoints shows a positional specificity. Abstract: Gamma-aminobutyric acid (GABA) is a major inhibitory neurotransmitter of the retina and affects myopic development. Electroacupuncture (EA) is widely utilized to treat myopia in clinical settings. However, there are few reports on whether EA affects the level of retinal GABA during myopic development. To study this issue, in the present study, we explored the changes of retinal GABA content and the expression of its receptor subtypes, and the effects of EA stimulation on them in a guinea pig model with lens-induced myopia (LIM). Our results showed that the content of GABA and the expression of GABAA and GABAC receptors of retina were up-regulated during the development of myopia, and this up-regulation was inhibited by applying EA to Hegu (LI4) and Taiyang (EX-HN5) acupoints. Moreover, these effects of EA show a positional specificity. While applying EA at a sham acupoint, no apparent change of myopic retinal GABA and its receptor subtypes was observed. Taken together, our findings suggest that LIM is effective to up-regulate the level of retinal GABA, GABAA and GABAC receptors in guinea pigs and the effect may be inhibited by EA stimulation at LI4 and EX-HN5 acupoints.